High-power triboelectric nanogenerator prepared from electrospun mats with spongy parenchyma-like structure. (April 2017) - Yu, Bin; Yu, Hao; Wang, Hongzhi; Zhang, Qinghong; Zhu, Meifang
Abstract: A triboelectric nanogenerator was prepared from electrospun polymer mats with a spongy parenchyma-like structure. The spongy parenchyma-like structure was imparted on the electrospun mats via cold-compacting post treatment. The optimized triboelectric nanogenerator attained a maximum electrical output, short circuit current, and load power of 695 V, 58 μA, and 3.1 W m −2, respectively. Energy harvesting from human slapping motion was used by the triboelectric nanogenerator to power an everyday scientific calculator. The mechanism of how the triboelectric power was enhanced by the spongy parenchyma-like structure is discussed, and is similar to the effect of an electret. The surface potential of the triboelectric nanogenerator based on an electrospun mat with a spongy parenchyma-like structure was higher than that based on an untreated electrospun mat. This triboelectric nanogenerator and its technology may have potential in portable electronics and flexible sensors. Graphical abstract: Highlights: The electrospun mat-based TENG with spongy parenchyma-like structure promoted the output performance. The spongy parenchyma-like structures made by cold-compacting increased the surface potential of triboelectic materials. It is potential to become an energy source to directly power portable electronic equipment, like a scientific calculator.